Assessment Of TV One Change Project For Analog Switch Off (ASO) Preparation Based On Dice Framework - Sjamsul Harun; M Taufiq Amir (Jurnal Scientia, 2024)
Broadcasting technology has change from analog to digital. In 2020, Indonesia government set out the deadline of analog switch off for every television station in 2 years. In change preparation, there are 2 (two) important factors i.e hard factor and soft factor. Both factor is needed to make change implementation successful. Sirkin (2005, p. 100) state that there is aspect has to give attention in the change process i.e hard factor. Hard factor in change management are duration, integrity, commitment and effort. It call DICE Framework. As one of the most famous television channel is Indonesia, tvOne got impact from analog switch off (ASO) regulation. This thesis try to formulate how the assessment of tvOne change projeck for analog switch off (ASO) preparation based on hard factor in change management (DICE Framework). The purpose of the research is to provide assessment of tvOne change project that have been done as analog switch off preparation. The methode in this research is case study and using qualitative approach. Result result has shown that tvOne is ready enough to run change project for analog switch off (ASO) preparation based of hard factor in change management (DICE Framework)